Managing NFS and NIS - Eisler, Mike (O'Reilly, 2011)
A modern computer system that's not part of a network is even more of an anomaly today than it was when we published the first edition of this book in 1991. But however widespread networks have become, managing a network and getting it to perform well can still be a problem. Managing NFS and NIS, in a new edition based on Solaris 8, is a guide to two tools that are absolutely essential to distributed computing environments: the Network Filesystem (NFS) and the Network Information System (formerly called the "yellow pages" or YP).